Tumour heterogeneity and intercellular networks of nasopharyngeal carcinoma at single cell resolution - Yang Liu (Nature Portfolio, 2021)
Nasopharyngeal carcinoma is a diverse cancer characterised by a heterogeneous microenvironment. Here, the authors use single cell sequencing to analyse the tumour microenvironment in 10 nasopharyngeal carcinoma tumours and identify different cell types including immune-suppressive T regulatory, tolerogenic dendritic, and exhausted CD8 T cells.